Controle da fusariose da pimenta-do-reino com aplicação de trichoderma harzianum - Oliveira, Carmelita dos Santos (2012)
The fusarium wil is a major disease of black pepper. Frequenttly it causes plant and, consequently, reduces yield, resulting in economic losses for black pepper producers. Considering the difficulties and limitations in controlling this disease, biological with Trichoderma spp. could be an alternative strategy to be inculded in the integrated disease management. The objective of this research was to evaluate the efficiency of Trichodermil® in controlling fusarium disease n crops of black pepper in the North of the Espírito Santo State in the city of São Mateus. The use of Trichodermil® reduced the disease in the field up to 50%. The mixture of organic matter suppliers compounds, with the exception of Polycana® , reduced the efficiency of Trichodermil® . The application intervals of 90 and 120 days were those with better control, at doses of 1 or 2 mL per plant.